Assessment of Alpha-Fetoprotein change in hepatoblastoma treatment in children - Truong, Dinh Khai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Objective: To evaluate the change of Alpha – Fetoprotein (AFP) levelsin the therapy process, in order to assess the efficiency of surgery and chemotherapy and a prognosis factor in children's hepatoblastoma treatment. Methods: Pre- respective study. This study focuses on 31 children hospitalized in Pediatric Hospital I, Il from January 2002 to April 2014, who were operated on and received chemotherapeutic treated post-op. followed by the same research pattern. Results: There were two groups: the survivors and the fatalities. In the survivor group, the difference of AFP level only appeared in cyacle 2, 3 with p<0.05, and had a special meaning in cycle 4 with p = 0.000. In this group, the AFP level decreased very quickly from cycle 1 to cycle 2, went down to normal digit at cycle 3and oscillatedaround the normal digit after 4 cycles. In the death group, the AFP level decreased at first, but it quickly increased at the end of the last cycle. Conclusion: The AFP level is much higher than 20ng/ml in all hepatoblastom children. Increasing the AFP level about ≥ 2logs or decreasing ≤ ten squared is a good prognosis in hepatoblastoma treatment process. The changing of AFP level help us to assess good efficiency or discover local relapsedtumorsor lung metastases.